Enforcement – Corporate Officer Liability – it is not a Walk in the Park and the The Foreign Corrupt Practices Act Application. Issue 2 (28th May 2017) - Termini, Roseann B.
Abstract: Criminal Strict Liability The Food Drug and Cosmetic Act is a public protection statute and provides for strict criminal liability. Therefore, corporate officials could be held criminally liable even if they had no knowledge or notice of the wrongdoing. The decision of Dotterweich concerned misbranded and adulterated drugs. The Supreme Court held that responsible corporate officials definitely could be prosecuted for violations and that strict liability applies under the Food Drug and Cosmetic Act (FDCA). This means that the court dispensed with a mens rea requirement or criminal intent usually requisite to sustain a criminal conviction. The jury at the trial court level found Mr. Dotterwiech, president and general manager, guilty of shipping misbranded drugs in interstate commerce and for shipping an adulterated drug. The Court of Appeals reversed the conviction and concluded that only the corporation was the 'person' subject to prosecution. Then, the United States Supreme Court reversed the Court of Appeals judgment and reinstated the conviction of the individual. United States v. Park is another landmark decision that involved criminal liability of corporate officials. The United States Supreme Court affirmed the imposition of criminal sanctions against a corporate official. That is, corporate officials can be held criminally accountable for failure to exercise authority and responsibility. The court determined that a corporate official has a duty to remedy violations and implement measures so that violations do not repeatedly occur. This articles addresses corporate liability under the FDCA and includes a discussion of the Foreign Corrupt Practices Act.